Uji Stabilitas Fisik dan Kimia Sediaan Tablet Paracetamol terhadap Suhu dan Kelembaban Selama Penyimpanan - Muhammad Hafiz Adha; Jaida Rahma; Nor Latifah (CV. ITTC INDONESIA, 2025)
This study aims to evaluate the physical and chemical stability of paracetamol tablets under varying temperature and humidity conditions, specifically room temperature (25°C ± 2°C) and high temperature (40°C ± 2°C) with relative humidity of 75% ± 5%. The stability test was conducted over a period of three months with observations at 30-day intervals. Parameters assessed included changes in color, tablet hardness, active ingredient content (measured using UV-Vis spectrophotometry), and pH of the dissolved solution. The results showed that tablets stored at high temperature experienced a decrease in paracetamol content by up to 5.8% and visible color changes starting from the second month. These findings highlight the importance of proper storage conditions to maintain the quality, safety, and efficacy of pharmaceutical products.